Study of liquid-liquid equilibria in aqueous two-phase systems formed by poly (ethylene glycol) (PEG) and sodium thiosulfate pentahydrate (Na2S2O3.5H2O) at different temperatures - Oliveira, Amanda Cristina de; Sosa, Filipe Hobi Bordon; Costa, Mariana Conceição da; Monteiro Filho, Elias de Souza [UNESP]; Ceriani, Roberta (Elsevier, 2018)
This study aimed at providing experimental liquid-liquid equilibrium (LLE) data for aqueous two-phase systems (ATPSs) formed by poly (ethylene glycols) (PEG) of different molecular weights (1500 or 4000 or 6000) g.mol−1 and sodium thiosulfate pentahydrate at different temperatures (293.15–313.15) K and under atmospheric pressure. Correlations of experimental data of binodal curves were carried out using the Merchuk methodology. The effects of temperature, polymer molecular weight and of the nature of the anion of salts on binodal curves were discussed. In comparison with other anions previously investigated, the salting-out ability of the thiosulfate anion was between those of citrate and tartrate anions. Finally, the Othmer-Tobias and Bancroft equations and the NRTL activity coefficient model were used for correlating tie line compositions.
Keywords: Aqueous two-phase systems (ATPS); Liquid-liquid equilibrium (LLE); Poly (ethylene glycol) (PEG); Sodium thiosulfate pentahydrate